Taxation and Accounting Consulting in Business Management - S. SHULHA (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2023)
The article is devoted to a study of taxation and accounting consulting in Ukrainian business entities. The study puts emphasis on central provisions of accounting and taxation records in business management, requiring due consideration in enhancing business performance. It outlines problematic aspects in the accounting and taxation system, resulting from the impact of the full-scale Russian invasion of the Ukrainian territory and triggering rapid change in the extremely sensitive financial and economic environment, with elaborating on their reflection in the law. It is shown that such fast flowing processes give rise to new flows of economic information, complicate mechanisms for the implementation of change and call for applications of a new toolkit designed to increase both the quality of accounting functions and tasks and the overall efficiency of business management system. In view of this, the need for using taxation and accounting consulting in Ukrainian business practices is demonstrated. The important role of consulting in business management when achieving strategic development goals is substantiated.